Human rights accountability of the association of South East Asian Nations (ASEAN). - Sean, Sok Phay. (2010)
This dissertation is about the problem of human rights accountability of the Association of South East Asian Nations (ASEAN). It seeks to trace the whereabouts of human rights accountability and understand why ASEAN has had less accountability to address the violation of human rights though it has adopted, ratified, and developed various instruments of human rights. The answer to this question is investigated by perusing existing human rights instruments and policies which ASEAN has developed, and by looking into the possibility of accountability mechanisms for human rights within ASEAN. A finding on four factors is derived from the existing literature on human rights and institutional accountability. The factors are commitment & transparency, participation, complaint & redress, and networking & monitoring.